Log-gases and random matrices - Forrester, P.J; Forrester, P.J (London Mathematical Society Monographs, 2010)
Random matrix theory, both as an application and as a theory, has evolved rapidly over the past fifteen years. Log-Gases and Random Matrices gives a comprehensive account of these developments, emphasizing log-gases as a physical picture and heuristic, as well as covering topics such as beta ensembles and Jack polynomials.